دور إدارة المعرفة في تعزيز الابداع التنظيمي - عمراوي, أم هاني; يوسف, فاطمة (University of Eloued جامعة الوادي, 2023)
هدفت هذه الدراسة إلى إبراز دور إدارة المعرفـــة في تعزيز الإبداع التنظيمي لدى أساتذة كلية العلوم الإنسانية والاجتماعيةجامعة الوادي، فانطلقت من التساؤل العام التالي: * كيف تساهم إدارة المعرفة في تعزيز الإبداع التنظيمي لدى أساتذة كلية العلوم الاجتماعية والإنسانية بجامعة الوادي؟ وقد تم الاعتماد على المنهج الوصفي التحليلي كونه الأنسب لموضوع الدراسة وتم استخدام الاستبيان الالكتروني كأداة لجمع المعلومات والبيانات حول متغيرات الدراسة، وتم نشره بالموقع الالكتروني لكلية العلوم الإنسانية والاجتماعية حيث اعتمدت الدراسة على عينة عشوائية بسيطة ليشمل مائة وسبعة وثلاثون(137) أستاذ دائم يمثلون مجتمع الدراسة،ولكن تم استرجاع 50 استبيان فقط تم اعتمادها كعينة دراسة ومن أجل اختبار الفرضيات تم استخدام التحليل الكمي. أما بخصوص نتائج الدراسة فكانت كالتالي: - لرأس المال البشري دور في تعزيز الإبداع التنظيمي لدى أساتذة كلية العلوم الاجتماعية والإنسانية بجامعة الوادي - للتطور التكنولوجي دور في تعزيز الإبداع التنظيمي لدى أساتذة كلية العلوم الاجتماعية والإنسانية بجامعة الوادي - يساهم تبادل المعلومات بين أفراد المنظمة في تعزيز الإبداع التنظيمي لدى أساتذة كلية العلوم الاجتماعية والإنسانيةبجامعة الوادي. الكلمات الافتتاحية: إدارة المعرفة،الإبداع التنظيمي،الرأسمال البشري،التطور التكنولوجي، تبادل المعلومات. Summary This study aimed to highlight the role of knowledge management in enhancing organizational creativity among professors of the Faculty of Humanities and Social Sciences, El-Oued University. It started from the following general question: * How does knowledge management contribute to enhancing organizational creativity among professors of the Faculty of Social Sciences and Humanities at El-Oued University? The analytical descriptive approach was relied on as it is most appropriate for the subject of the study. The electronic questionnaire was used as a tool for collecting information and data about the variables of the study. It was published on the website of the College of Humanities and Social Sciences. The study relied on an intentional cross-sample to include one hundred and thirty-seven (137) permanent professors representing the study community. However, only 50 questionnaires were retrieved and used as a study sample, and in order to test the hypotheses, quantitative analysis was used.As for the results of the study, they were as follows: -Human capital has a role in enhancing organizational creativity among professors of the Faculty of Social Sciences and Humanities at El-OuedUniversity -Technological development has a role in enhancing organizational creativity among professors of the Faculty of Social Sciences and Humanities at El-OuedUniversity - The exchange of information between the members of the organization contributes to enhancing the organizational creativity of the professors of the Faculty of Social Sciences and Humanities at El-OuedUniversity. Key Words: knowledge, creativity, knowledge management, organizational creativity, human capital, technological development, information exchange.
دراسة ميدانية لاساتذة كلية العلوم الاجتماعية والانسانية بجامعة الوادي
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: ادارة المعرفة، Gestion des connaissances, knowledge management; الإبداع التنظيمي، créativité organisationnelle, Organizational creativity